Bom Bunuh Diri: Antara Jihad dan Teror - Imam Mustofa (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2011)
Policy of western countries, especially the United States against some Muslim countries in the Middle East region led to a backlash and generate assistance in various ways. One way or form of resistance which is by suicide bombing. Even this kind of action does not only happened in the region or the state which is being colonized or war zone, but also often happened in a peaceful country like Indonesia. This paper attempt to uncover the law suicide bombing in perspective of Islamic law by classifying into two, the first suicide bombing as a jihad and second, suicide bombings as terror. This article tries to answer the questions when suicide bombing can be categorized as jihad? What are the conditions or requirements? And when its categorized as terror? The answer in this paper derived from qualitative research. This research is library research toward source texts of Islam, including the fatwas and opinions of ulama, especially contemporary ulama. Author using a theory of maÅŸlahah which is the purpose of shari'a (maqashid al-syariah) as basis for reviewing the legal and categorized of suicide bombing. When a suicide bombing itself include maÅŸlahah by meeting various condition or requirements, then it is categorized as jihad. However, when its performed in peaceful area causes damage that reduces maÅŸlahah, suicide bombing is categorized as terror.